RANCANG BANGUN SISTEM PEMANFAATAN PANAS BUANG PADA KOMPOR PORTABEL MENGGUNAKAN THERMOELECTRIC GENERATOR - Hudaya, Chairul (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2021)
The world's population continues to grow, causing energy needs to increase rapidly.In fact, not all regions have a special supply of electrical energyareas that are located in remote and difficult to access places. Besides the depletion of reservesfossil fuels as the main source of electricity generation and effectsbad pollution also encourages the change of energy sources into new energyrenewable (EBT). The purpose of this research is to design a solution forovercome both of these by using the exhaust heat utilization system(waste-heat recovery) in domestic combustion, especially portable stoves.Thermoelectric generator (TEG) is the right choice because it has severaladvantages needed such as simple conversion process, reliabilityhigh, and ease of application. The research will discuss the design of the toolwaste-heat recovery on portable stoves mechanically and electrically. Designcarried out on 2 different types of TEG modules, namely TEP1-1264-3.4 and SP1848-27145. The proposed tool has an estimated output power of about 9.24 W for the moduleTEP1-1264-3.4 and 9.0048 W for SP1848-27145 module using 8a TEG module with an approximate temperature difference of 60 ? and a cooling systemwater based. Thus the TEP1-1264-3.4 module generates more powerhigher than SP1848-27145 module and the series configuration is rated better because of thishave no problem when experiencing voltage differences between modules. Designmechanical build that is made to have 2 separate frame parts for conveniencecircuit maintenance.